MENYIMAK PENOMENA PEMANASAN GLOBAL/PERUBAHAN IKLIM (La-Nina), ALIH FUNGSI LAHAN DAN MITIGASI KERUSAKAN LINGKUNGAN DI PULAU BALI - Kasa, I Wayan; Gunam, Ida Bagus Wayan (SIMBIOSIS, 2019)
Up to now Bali island still suffering from light to heavy rainfall (August 2016), eventhough it must be hot season as usual (April to October). Such situation is recognised as La-Nina phenomenon. Methode empolyed in this study is collecting primary (direct field check) and scondary data (literature study). Results showed that, the La-Nina phenomena most affected coffee plantation farmers in the village of Sepang, district of Busungbiu, Buleleng regency. The coffee fruit fall out from stem branch prior to harvest time and becoming black in colour. In addition, some coffee fruit skin are white in colour in comparison to red to black during normal hot season. Land use change could also be seen over Bali. Increase sea level on some beaches are also another disaster around Bali. Such accidence was significantly happened on the beach of Lepang village, district of Banjarangkan, Klungkung regency. It was found that such increases puddling area of more or less five hectare of paddy rice field on that area. The global warming/climate change phenomenon  also cause habitat loss of specific ancient crab who live in Nusa Penida beach and move into the Giri Putri holy cave to survive. However, the only government do to compromise and mitigate such abnormal environmental degradation would be by strengthening the essen of the Eka Karya botanical garden of Bedugul as an open green field area for refreshing.